NILAI ANAK, STIMULASI PSIKOSOSIAL, DAN PERKEMBANGAN KOGNITIF ANAK USIA 2-5 TAHUN PADA KELUARGA RAWAN PANGAN DI KABUPATEN BANJARNEGARA, JAWA TENGAH - Dwi Hastuti; Alfiasari Alfiasari; Chandriyani Chandriyani (Jurnal Ilmu Keluarga dan Konsumen, 2010)
Optimal growth and development during early childhood will be able to describe a better future, especially for children between 2-5 years old. The aim of the study was to analyze value of child, psychosocial stimulation, and cognitivedevelopment of 2-5 years old children in food insecurity areas at district of Banjarnegara, Jawa Tengah Province. Two subdistrict which were Pejawaran and Punggelan were selected purposively. From each subdistrict, 3 villages were chosen for a total of 6 villages served as site of the study. From each villages, 50 families with its children aged 2-5 years were randomly selected, for a total of 300 families as respondents of this study. Result showed that average score of value of children was 81,2%. It means that parents had high of perception and expectation to their children. Meanwhile, average score of psychosocial stimulation for 2-3 years old children was 49,8% and for 3-5 years old children was 57,4%. The average score of cognitive development for 2-5 years old children was 50,6%, which indicated that children still had low cognitive development. There was significant and possitive correlation between value of children and psychosocial stimulation. In line with this, increasing of psychosocial stimulation score was followed by increasing of child cognitivedevelopment score. Result showed that cognitive development was significantly and positively influenced by length of maternal education, length of child’s participation on preschool education, family economic status, and psychosocial stimulation. On the other hand, increasing of age of children will be followed by decreasing score of cognitive development.